(untitled) (MAUSAM, 1988)
Crustal velocity models have been evaluated for the Koyna region based on DSS explosion, by IMD (Srivastava et al. 1984) and NGRI (Kaila et al. 1981) by comparing the epicentral parameters of well recorded earthquakes of magnitude>.4 through HYPO.71 computer programme. The location of 4 large explosions has also been computed by these two models. The hypocentral parameters of the main Koyna earthquake of December 1967 have also been discussed whose focal depth was reported about 2 km (Srivastava 2nd Dube 1982) based on P-wave arrival time only. It is inferred that IMD’s model with P and S wave velocities/structures provide better results in the monitoring of micro-earthquake activity and their source mechanism in the vicinity of Koyna reservoir.